Proceedings of the 7th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2019
DOI: 10.7712/120119.7110.20034
|View full text |Cite
|
Sign up to set email alerts
|

Rintc-E Project: Towards the Seismic Risk of Low and Pre-Code Single-Story Rc Precast Buildings in Italy

Abstract: This paper reports the preliminary results of a research project (RINTC-E) aimed at computing the risk of collapse in RC precast industrial buildings designed according to the codes in force in Italy in Seventies and Nineties. Companion papers describe the overall research project, funded by the Italian Civil Protection Department, its different areas of application (reinforced concrete, masonry, steel buildings, etc), and the overall seismic risk calculation procedure. This paper describes the design, modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In particular, q decreases from 2.88, to 2.49 with a collapse limit 80% of , and to 1.84 with a collapse limit 60% of . These results clearly depend on the ultimate rotation limits predicted by Equation (2), which are not specific for existing precast columns, therefore, additional research is necessary in order to find more suitable formulations to be applied to this structural typologies, as recognized also by Magliulo et al [45].…”
Section: Behavior Factor Estimationmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, q decreases from 2.88, to 2.49 with a collapse limit 80% of , and to 1.84 with a collapse limit 60% of . These results clearly depend on the ultimate rotation limits predicted by Equation (2), which are not specific for existing precast columns, therefore, additional research is necessary in order to find more suitable formulations to be applied to this structural typologies, as recognized also by Magliulo et al [45].…”
Section: Behavior Factor Estimationmentioning
confidence: 97%
“…Since the columns are prefabricated, with continuous longitudinal bars, it is not possible to consider the third correcting coefficient. All this enhances the necessity to evaluate other types of significant reduction coefficients to be proposed in this formula for the specific case of existing prefabricated elements not designed with anti-seismic standards, for which additional research may be required [44,45].…”
Section: Properties Of the Plastic Hingesmentioning
confidence: 99%
“…For further structural verifications, not available or not fully addressed in the Italian building code, Eurocode 2 (CEN, 2004), Eurocode 3 (CEN, 2004), CNR 10018/99 and CNR 10025/98 provisions were considered, particularly in respect to dowel capacity. Other details regarding the geometry of the selected case study may be found in Magliulo et al (2019).…”
Section: Considered Case Studymentioning
confidence: 99%
“…At this regard, a case study resembling a typical precast industrial building was selected and a multiple-stripe analysis was carried out. The current research is part of an Italian national project, namely RINTC (Bracchi et al, 2019;Cantisani and Della Corte, 2019;Iervolino et al, 2019;Magliulo et al, 2019;Ragni et al, 2019;Ricci et al, 2019), aiming at assessing the failure rate of various construction typologies designed in accordance with modern anti-seismic regulations (specifically the Italian building code, NTC18, 2018), therefore estimating the implicit risk of codeconforming buildings. Specifically, the comparison of the collapse rates of the investigated comprehensive 3D model with models accounting for simplified assumptions (such as those used in the RINTC project) allows validating the simplifying assumptions, such as in the case of the dowel beam-to-column connections, in order to obtain good estimates of the structural failure rate while reducing the computational effort.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed the performance of existing precast structures and how to make them earthquake proof [14], [15], [16], [17], [18], [19], [20], [21]. The research presented herein is aimed at evaluating the failure probability of new precast structures designed according to the current Italian seismic regulations as part of a national project financed by the Italian Civil Protection focused on the assessment of new and existing buildings [22], [23], [24], [25], [26], [27]. The influence of different modelling strategies on the failure rate are analyzed taking as reference a typical precast building.…”
Section: Introductionmentioning
confidence: 99%